2010
DOI: 10.1007/s12031-010-9332-2
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptional Profiling in the Lumbar Spinal Cord of a Mouse Model of Amyotrophic Lateral Sclerosis: A Role for Wild-Type Superoxide Dismutase 1 in Sporadic Disease?

Abstract: Mice bearing mutations of copper-zinc-superoxide dismutase recapitulate spinal cord motor neuron degeneration and disease progression occurring in human amyotrophic lateral sclerosis. We have investigated the relationship between disease progression and altered gene expression by comparing the transcriptional profiles in lumbar spinal cord, fronto-parietal cortex and hippocampus of mutant G93A-SOD1, wild-type SOD1 transgenic and non-transgenic mice. Gene expression was evaluated at 55 and 110 days of age, repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
3
16
0
1
Order By: Relevance
“…Curiously, the expression of genes involved in cell death pathways was not significantly up-regulated specifically within motor neurons, indicating that the loss of these cells is a late event in the disease [44, 45]. Finally, the pattern of gene expression in the spinal cord of SOD1(G93A) mice at end stage was very similar to that found in post-mortem specimens of human ALS, and affected genes involved in cell death [25, 43, 47] and neuroprotection [43, 44], inflammation [25, 43, 47], proteasome function [25, 42, 43], metabolism [25, 42, 47], cytoskeleton and axonal guidance [25, 42-44, 47] (Fig. 1 ).…”
Section: Transcriptomics For the Analysis Of Als Pathogenesismentioning
confidence: 92%
See 1 more Smart Citation
“…Curiously, the expression of genes involved in cell death pathways was not significantly up-regulated specifically within motor neurons, indicating that the loss of these cells is a late event in the disease [44, 45]. Finally, the pattern of gene expression in the spinal cord of SOD1(G93A) mice at end stage was very similar to that found in post-mortem specimens of human ALS, and affected genes involved in cell death [25, 43, 47] and neuroprotection [43, 44], inflammation [25, 43, 47], proteasome function [25, 42, 43], metabolism [25, 42, 47], cytoskeleton and axonal guidance [25, 42-44, 47] (Fig. 1 ).…”
Section: Transcriptomics For the Analysis Of Als Pathogenesismentioning
confidence: 92%
“…Of note, the expression of the intermediate filament vimentin was consistently found to be up-regulated in several studies [25, 42, 45]. Vimentin plays an important role in the organization of the cytoskeleton and interacts with dynein to mediate neurite outgrowth [46].…”
Section: Transcriptomics For the Analysis Of Als Pathogenesismentioning
confidence: 99%
“…However, overexpression of wild type SOD1 in mice does not result in disease, although mitochondrial alterations and subclinical defects are observed at older ages (88). Also, alterations in gene expression in the spinal cord were reported for mutant and WT SOD1 models but not in nontransgenic mice (89). Large aggregates of SOD1 are generally observed in fALS, but have only been reported for a subset of sALS cases (4,5,90), and are not detected by SEDI in sALS (90).…”
Section: Aggregation Arising From Holo Sod1 Is Not Different Frommentioning
confidence: 99%
“…Compared to several other ALS microarrays (Brockington et al 2010; Chen et al 2010; Cox et al 2010; D’arrigo et al 2010; Ferraiuolo et al 2007; Ferraiuolo et al 2011; Gonzalez De Aguilar et al 2008; Jiang et al 2005; Kirby et al 2005; Kudo et al 2010; Vargas et al 2008; Yoshihara et al 2002), we identified five genes from our ≥2-fold change list that have orthologs in SOD1 transgenic mice and human patients with sporadic ALS (Table 1). Sepia is the fly ortholog of mouse glutathione S-transferase omega 1 (O’brien et al 2005) and was up-regulated in 45d flies with G85R in glia and MN+glia but was down-regulated in mouse motoneurons (Kirby et al 2005).…”
Section: Resultsmentioning
confidence: 99%